Contact interaction of elastic strips with initial stresses with a infinite and finite stringers - Dikhtyaruk, N.N.; Poplavskaya, E.A.; Kurinyenko, O.V. (Problems of Tribology, 2019)
The present article the problems of the contact interaction of infinite and finite elastic stringer with a prestressed elastic strip. The study is performed in the framework of the linearezed theory of elasticity in common form for the theory of large (finite) initial deformations and two variants of the theory of small initial deformations with elastic potential of arbitrary structure. Based on the assume that the stringers load at the same time the vertical and horizontal forces, fair model of bending beams in combination with horizontall elongation. This problem is mathematically formulated as a system of integro-differential equations of a relatively unknown contact stresses. The system is solved in a closed forms using transformation of Fourier. Expressions of stresses are represented by Fourier integrals with a simple enough structure. Influence of initial stress on the distribution of contact stresses is study and discovered the mechanical effects under the influence of concentrated loads.